Optimal Timing for Oocyte Denudation and Intracytoplasmic Sperm Injection - Catherine Patrat; Aida Kaffel; Lucie Delaroche; Juliette Guibert; Pierre Jouannet; Sylvie Epelboin; Dominique De Ziegler; Jean-Philippe Wolf; Patricia Fauque (Obstetrics and Gynecology International)
Objectives. To analyze the impact of oocyte denudation and microinjection timings on intracytoplasmic sperm injection (ICSI) outcomes. Study Design. We included ICSI cycles with the following parameters: rank 1 or 2, female age <36 years, male factor infertility, long protocol using GnRH agonist and rFSH for ovarian stimulation, and use of freshly ejaculated sperm (𝑛=110). Several ICSI parameters were analyzed according to the time between oocyte retrieval and denudation (𝑇1) and the time between denudation and ICSI (𝑇2) using a statistical logistic regression analysis. Results. Neither 𝑇1 nor 𝑇2 had a significant influence on the Metaphase II (MII) rate but the fertilisation rate (FR) showed a significant improvement when 𝑇1 was longer (optimal results at 𝑇1=3 hours) while FR significantly decreased with the increase of 𝑇2. Optimal implantation (IR) and pregnancy (PR) rates were obtained when 𝑇1 was around 2 hours. Conclusion. Incubation of oocytes around 2 hours between retrieval and denudation may not increase MII rate but appears to lead to the optimal combination of FR and IR.